Getting the angles straight in speed skating: a validation study on an imu filter design to measure the lean angle of the skate on the straights - van der Kruk, E.; Schwab, A. L.; van der Helm, F. C. T.; Veeger, H. E. J. (Procedia Engineering, 2016)
To assist speed skaters in improving their skating performance, we would like to provide them with real time feedback on the orientation of the skate within a single stroke. While of course the forces generated by the skater on the ice determine the acceleration of the skater, the orientation of the skate determines in which direction this force, and thus acceleration, is headed. In this study we focus on the validation of the lean angle measurements of the skate, which distributes the push-off forces over the global vertical and transverse component. To measure this angle, an inertial measurement unit (IMU) would be a logical choice, but two aspects render measuring with commercially available IMUs and their filters on an ice rink rather difficult, first the ferromagnetic materials in the vicinity of the IMU and secondly the large linear accelerations. In this paper we therefore propose filters that bypass these problems. In total three complementary filters with adaptive gain were validated with a motion capture system. The filter based on the assumption that the lean angle can be reset to zero (upright) when there is no change in steer angle of the skate, showed the most accurate results (mean RMSE error of 5.30 and 3.60, for the left and right skate respectively). Integrated into the filter is an IMU based stroke detection, which as a stand-alone system could provide feedback on stroke frequency, stroke length, contact time or double stance phase time. It is concluded that an IMU used with this filter can provide individual elite speed skaters reliable feedback on their skate lean angle.